Rebuilding Climate Authority: A Neo Khaldunian Framework of Asabiyya and Mulk - Gregory Yehezkiel Marhaendra (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2026)
In Scientists view the climate crisis as an urgent emergency, yet many government policies move slowly and can easily shift direction. In this context, Ibn Khaldun’s theoretical framework helps explain why collective commitment weakens and why authority often fails to prioritise long term protection. This study aims to analyse a Neo Khaldunian framework to explain the social foundations of climate governance and to guide institutional design that can strengthen solidarity, asabiyya, and redirect authority, mulk, toward ecological stewardship. The study uses an integrative literature review with a critical interpretive approach to develop a theoretical framework, rather than to test hypotheses with field data. The data were collected purposively from peer reviewed journal articles, scholarly books, and major reports, including selected studies on Islamic environmental politics in Indonesia and other Muslim contexts, through Google Scholar and Scopus. The analysis proceeded through repeated reading, comparison, conceptual grouping, and critical synthesis that connects scholarship on climate governance, social solidarity, sociology of religion, and Ibn Khaldun. The findings show that climate governance failure can be understood as a problem of civilisational order unfolding across five dimensions, namely ideas, individuals, society, the state, and civilisation. The study also finds that the erosion of asabiyya and the distortion of mulk undermine ecological commitment, while Islamic institutions, as contested organisational actors, can strengthen or weaken commitment through networks, legitimacy, organisational capacity, public influence, and political alliances. The sociological implication is that climate governance should be understood as a problem of social order and legitimacy, so institutional design that protects long term commitments becomes essential. Para ilmuwan menilai krisis iklim sebagai keadaan mendesak, tetapi banyak kebijakan pemerintah berjalan lambat dan mudah berubah. Dalam konteks ini, kerangka teori Ibn Khaldun membantu menjelaskan mengapa komitmen bersama melemah dan otoritas sering tidak fokus pada perlindungan jangka panjang. Penelitian ini bertujuan untuk menganalisis kerangka Neo Khaldunian guna menjelaskan dasar sosial tata kelola iklim dan memberi arah desain lembaga yang dapat memperkuat solidaritas asabiyya serta mengarahkan otoritas mulk menuju pengelolaan ekologis. Penelitian ini menggunakan tinjauan literatur integratif dengan pendekatan interpretif kritis untuk menyusun kerangka teoretis, bukan untuk menguji hipotesis dengan data lapangan. Data dikumpulkan secara purposif dari artikel jurnal, buku ilmiah, dan laporan utama, termasuk studi terpilih tentang politik lingkungan Islam di Indonesia dan konteks Muslim, melalui Google Scholar dan Scopus. Analisis dilakukan lewat pembacaan berulang, perbandingan, pengelompokan konsep, dan sintesis kritis yang menghubungkan literatur tata kelola iklim, solidaritas sosial, sosiologi agama, dan kajian Ibn Khaldun. Hasil penelitian menunjukkan bahwa kegagalan tata kelola iklim dapat dipahami sebagai masalah tatanan peradaban dalam lima dimensi, yaitu ide, individu, sosial, negara, dan peradaban. Temuan juga menunjukkan bahwa melemahnya asabiyya dan menyimpangnya mulk merusak komitmen ekologis, sementara institusi Islam sebagai aktor organisasi yang diperebutkan dapat memperkuat atau melemahkan komitmen melalui jejaring, legitimasi, kapasitas organisasi, pengaruh publik, dan aliansi politik. Implikasi sosiologisnya adalah isu iklim perlu dipahami sebagai masalah keteraturan sosial dan legitimasi, sehingga desain lembaga yang menjaga komitmen jangka panjang menjadi hal penting.